1988
DOI: 10.1172/jci113577
|View full text |Cite
|
Sign up to set email alerts
|

Multiple components of the A1 adenosine receptor-adenylate cyclase system are regulated in rat cerebral cortex by chronic caffeine ingestion.

Abstract: The effects of chronic caffeine on the Al adenosine receptoradenylate cyclase system of rat cerebral cortical membranes were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 41 publications
5
32
1
Order By: Relevance
“…On the other hand, absence of such alterations has been also reported (Georgiev et al, 1993;Von Lubitz et al, 1994a,b). Since prolonged exposure to adenosine m I receptor agonists causes uncoupling of G-proteins from the receptor (Ramkumar et al, 1988), downregulation of cellular levels of G-proteins, or their redistribution from the membranes to the cytosol (Milligan, 1993), it has been suggested that the regimen-dependent inversion of the therapeutic outcome may result from changes induced in G-proteins (Von Lubitz et al, 1994a,b).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, absence of such alterations has been also reported (Georgiev et al, 1993;Von Lubitz et al, 1994a,b). Since prolonged exposure to adenosine m I receptor agonists causes uncoupling of G-proteins from the receptor (Ramkumar et al, 1988), downregulation of cellular levels of G-proteins, or their redistribution from the membranes to the cytosol (Milligan, 1993), it has been suggested that the regimen-dependent inversion of the therapeutic outcome may result from changes induced in G-proteins (Von Lubitz et al, 1994a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that a series of daily injections of CPA results in facilitation of learning possibly caused by downregulation of A 1 receptor sites. Conversely, therefore, chronic exposure to an adenosine receptor A 1 antagonist may upregulate them (Ramkumar et al, 1988) with the consequent impairment of memory functions. Interpretation of the results obtained when drugs were administered prior to training is more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that chronic treatment with caffeine causes an upregulation of adenosine A, receptors (Fredholm, 1982;Johansson et al, 1993a;Shi et al, 1993). There is also evidence that receptors for other transmitters, especially GABA and ACh, as well as G,-proteins are affected (Ramkumar et al, 1988;Shi et al, 1993). Interestingly, both NGFI-A and NGFI-B proteins can bind specifically to DNA (Christy and Nathans, 1989;Wilson et al, 1991) and act as transcription factors.…”
Section: Gaba Releasementioning
confidence: 99%